24 hour ambulatory blood pressure monitoring and left ventricular ejection fraction- prognostic markers in chronic kidney disease - Choudhary, Lekharaj; Gupta, Poonam; Gupta, Arvind; Saxena, Piyush; Chaurasia, Ajeet K. (International Journal of Advances in Medicine, 2017)
Background: Left ventricular systolic dysfunction i.e. <55% is common and an important predictor of risk of cardiac death in chronic kidney disease patients. Ambulatory blood pressure monitoring assists in targeting this population. Methods: Total 160 non diabetic hypertensive patients were enrolled between 10/04/14 to 15/05/15 at M.L.N. Medical College and SRN Hospital, Allahabad, India. Out of them 80 were CKD patients who were taken as cases and remaining 80 patients were non CKD and taken as controls. Ambulatory blood pressure monitoring, clinic BP, eGFR, %LVEF (left ventricular ejection fraction) and other clinical data were collected for 1 year duration. Statistical analysis was done by using unpaired t-test for independent variables. Results: Out of 160 non diabetic hypertensive patients, 48 (60%) cases and 28 (35%) controls were found non-dippers, while remaining 32 (40%) cases and 52 (65%) controls were have dipper BP pattern. Patients with non-dipping BP pattern and low %LVEF had the worst renal function and severe cardiovascular damages (P<0.05). The eGFR and %LVEF shown significant relationship with the rate of decline in nocturnal BP. Conclusions: Ambulatory blood pressure measurement allows a better risk stratification compared to clinic blood pressure measurement. Non-dipping status and low LVEF is closely related to severe renal and cardiovascular damage in CKD patients. Low LVEF and 24-hour ABPM can be used as prognostic markers in non-diabetic CKD patients, and lowering of nocturnal BP will reduce the renal and cardiovascular risk in these patients.